2019
DOI: 10.1542/hpeds.2017-0237
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Antibiotic Selection and Clinical Outcomes in Infants <60 Days Hospitalized With Skin and Soft Tissue Infections

Abstract: A B S T R A C TOBJECTIVES: To describe variation in empirical antibiotic selection in infants ,60 days old who are hospitalized with skin and soft-tissue infections (SSTIs) and to determine associations with outcomes, including length of stay (LOS), 30-day returns (emergency department revisit or readmission), and standardized cost. METHODS:Using the Pediatric Health Information System, we conducted a retrospective study of infants hospitalized with SSTI from 2009 to 2014. We analyzed empirical antibiotic sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…Our study cohort included relatively few neonates, and thus our findings may not be applicable to this population subgroup. We chose not to include regimens with third‐generation cephalosporins or ampicillin, which may have limited the number of included neonates, because these antibiotics are frequently administered during evaluation for invasive bacterial infections 23 . We found a very low occurrence of treatment failure in our study cohort across all three groups, which is consistent with other studies of SSSS that report an overall good prognosis and low recurrence and/or readmission rates 6,16,24 .…”
Section: Discussionsupporting
confidence: 82%
“…Our study cohort included relatively few neonates, and thus our findings may not be applicable to this population subgroup. We chose not to include regimens with third‐generation cephalosporins or ampicillin, which may have limited the number of included neonates, because these antibiotics are frequently administered during evaluation for invasive bacterial infections 23 . We found a very low occurrence of treatment failure in our study cohort across all three groups, which is consistent with other studies of SSSS that report an overall good prognosis and low recurrence and/or readmission rates 6,16,24 .…”
Section: Discussionsupporting
confidence: 82%
“…The first was a retrospective study by Markham et al of infants hospitalized with skin and soft-tissue infections (SSTI), in which a wide variation in empirical antibiotic selection has been noted: clindamycin was the most commonly used staphylococcal antibiotic, whereas 21.4% of patients received vancomycin. However, they did not discuss the management of different conditions because the aim of the study was to describe empirical antibiotic selection in infants with SSTI across 36 children’s hospitals and investigate the association of different empirical antibiotic regimens with the length of hospital stay, readmission rates, and costs [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of treatment failure in this study falls within the range of treatment failure rates described by several retrospective studies of young infants less than 60 days of age with SSTIs (0%-9.3%). 3,[15][16][17] Two of the studies with lower treatment failure rates (0%-0.8%) included only culture-proven S aureus SSTIs and a large proportion of neonates with pustulosis, which can often be treated solely with topical antibiotics and likely contributed to the lower rate of treatment failure. 15,16,18,19 The other 2 larger retrospective multicenter studies based on administrative billing data in children's hospitals found a similar occurrence of treatment failure in neonates with SSTIs of 9.2% to 9.3%.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Prior studies report that clindamycin is commonly used for treatment as a component of therapy for SSTIs in neonates, making SSTIs an ideal condition for further study of enteral antibiotic use in this population. [15][16][17] The Infectious Diseases Society of America recommendations for neonates with Staphylococcus aureus SSTIs are extrapolated from adults and children, with no specific recommendations regarding oral therapies, indicating the need for further evidence. 18 The purpose of this study is to determine the frequency of treatment failure in neonates receiving IV and oral antibiotic therapy for uncomplicated SSTIs and explore patient and SSTI-related characteristics associated with treatment failure, including the oral antibiotic regimen and factors that may influence enteral absorption of oral antibiotics.…”
Section: Introductionmentioning
confidence: 99%